Renal cell carcinoma harboring somatic TSC2 mutations in a child with methylmalonic acidemia. Issue 5 (17th October 2016) - Potter, Samara L.; Venkatramani, Rajkumar; Wenderfer, Scott; Graham, Brett H.; Vasudevan, Sanjeev A.; Sher, Andrew; Wu, Hao; Wheeler, David A.; Yang, Yaping; Eng, Christine M.; Gibbs, Richard A.; Roy, Angshumoy; et al.
Abstract: Pediatric renal cell carcinoma (RCC) is a rare cancer that can be associated with inherited diseases including tuberous sclerosis complex (TSC) caused by germline mutations in TSC1 or TSC2 . Somatic mutations in TSC1 and TSC2 have also been reported in adult RCC, which predict response to mTOR inhibitors. Here, we present the first case of RCC in a child with methylmalonic acidemia (MMA). Clinical whole exome sequencing of blood and tumor samples confirmed the diagnosis of MMA and revealed two somatic inactivating mutations in TSC2, suggesting the potential consideration of an mTOR inhibitor in the event of tumor recurrence.